STRUKTUR KOMUNITAS TUMBUHAN OBAT PASCAPERSALINAN DI PEKARANGAN MASYARAKAT SUNDA DESA CIBURIAL, BANTEN - Siti Dian Rosadi; Nisyawati; Afiatry Putrika (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2020)
Has conducted research on the structure of postpartum medicinal plants in the yard of the Sundanese community of Ciburial Village. Research developed to study what garden plants are used in postpartum medicine, as well as how they are in the yard. The research method used includes interviews and vegetation analysis. Interview results show that the plants used by the Sundanese community of Ciburial Village for the treatment of postpartum reached 46 species. Vegetation analysis results showed that as many as 36 species of post-delivery medicinal plants were obtained from the yard. Medicinal plants that have the highest Importance Value Index (INP) in the liana group are Areuy Hatta (Lygodium circinatum), terna group namely nampong (Siegesbeckia orientalis), shrub group namely harendong (Melastoma malabathricum), and these groups are called kalapa (Cocos nucifera ). Keywords: Banten, Ciburial, Yard, Medicine, Postpartum